Interdisciplinary Approaches for Sustainable Development Goals Economic Growth, Social Inclusion and Environmental Protection (GeoPlanet: Earth and Planetary Sciences,, 2018)
This book discusses the impacts of climate change that are already being felt on every continent and provides the scientific basis for a number of modern approaches and state-of-the art methods for monitoring the environment, social behavior and human expectations concerning protection of the environment. The book approaches these issues from the perspectives of various disciplines, from physics to the social sciences, and highlights both current challenges and future prospects. On 1 January 2016, the 17 Sustainable Development Goals (SDGs) defined in the 2030 Agenda for Sustainable Development - 12 of which involve taking action on climate change - officially came into force. To achieve sustainable development, it is and will remain crucial to harmonize three interconnected core elements: economic growth, social inclusion and environmental protection.